The Effectiveness of Zepeto Game to Improve Students Speaking Skill - Afifah Nur Hidayati; Abdul Muin; Eulis Rahmawati (Wanastra: Jurnal Bahasa dan Sastra, 2023)
The purpose of this study was to determine the impact of Zepeto Game learning media on speaking skills in the second grade of MA Annida Al-Islamy Jakarta Barat. This study employed a quasi-experimental design with two classes as the sample. Furthermore, the research design of this study includes a pre-test, treatment, and post-test, with the XI MIPA 1 class acting as the experimental class and the XI MIPA 2 class acting as the control class. The researcher used 60 second-grade students as respondents to accomplish the goal of this study. They were then split into two groups: experimental and control. During the treatment process, the experimental group received Zepeto Game as learning media, while the control group received traditional instruction. According to the t-test calculation, to = 6,06 is greater than tt = 2,39, in the degree of significance 1% = 2,39, and in the degree of significance 5% = 1,67.